The Screening Azotobacter Spp., Bioavailability from Four Ecological Systems in Zakho Town, Kurdistam Region – Iraq - Issa, Fawzi Adil; K. Ramadhan, Zozan (Science Journal of University of Zakho, 2022)
This project was designed to analyse the impact of several environmental factors on the Azotobacter abundance in soil samples.  Azotobacter spp. were isolated from four ecological systems and screened for calculating CFU numbers per two grams of soil. Soil samples with a range of textures were collected from Zakho town (Kurdistan Region – Iraq). Soil particle sizes distributions were measured as (% sand, % silt and % clay). Soil chemical and physical features like (pH, electrical conductivity, organic matters availability) in addition to various soil textures; Loam (4 samples), clay (3 samples), silt (1 sample), clay loam (4 samples) were determined. Electrical conductivity measurements were fallen between 35.7 dSm-1 in sample (L2) and 5.17 dSm-1 in sample (C2). Organic matters availability was from 17.6% in sample (C2) to 4.18% as in sample (R3). Soil samples' pH values were between 9.41 as in sample (R2) and 7.72 that found in sample (L3). Concerning all growth impact factors, the maximum number (370 CFU) of Azotobacter was observed in the R1 sample. No Azotobacter growth was observed in samples; G1 and G2 while sample G3 produced (55 CFU). All isolates show stable growth from the legume rhizosphere zoon (L1 105-, L2 60-, and L3 125-CFU). No isolates were obtained from the R2 soil sample while only 70 CFU were seen in the R3 sample. Samples; C1 and C3 formed 94 and 108 CFU respectively whereas no isolated colonies were noticed in the C2 soil sample.
Keywords: Soil; soil texture; soil bacteria; Azotobacter; legume; pH; bacterial density; Zakho; Kurdistan-Region; Iraq